Influences on neural lineage and mode of division in the zebrafish retina in vivo - Poggi, Lucia (The journal of cell biology, 2005)
Cell determination in the retina has been under intense investigation since the discovery that retinal progenitors generate clones of apparently random composition (Price, J., D. Turner, and C. Cepko. 1987. Proc. Natl. Acad. Sci. USA. 84:156-160; Holt, C.E., T.W. Bertsch, H.M. Ellis, and W.A. Harris. 1988. Neuron. 1:15-26; Wetts, R., and S.E. Fraser. 1988. Science. 239:1142-1145). Examination of fixed tissue, however, sheds little light on lineage patterns or on the relationship between the orientation of division and cell fate. In this study, three-dimensional time-lapse analyses were used to trace lineages of retinal progenitors expressing green fluorescent protein under the control of the ath5 promoter. Surprisingly, these cells divide just once along the circumferential axis to produce two postmitotic daughters, one of which becomes a retinal ganglion cell (RGC). Interestingly, when these same progenitors are transplanted into a mutant environment lacking RGCs, they often divide along the central-peripheral axis and produce two RGCs. This study provides the first insight into reproducible lineage patterns of retinal progenitors in vivo and the first evidence that environmental signals influence the orientation of cell division and the lineage of neural progenitors.